2010
DOI: 10.1088/0004-637x/716/1/131
|View full text |Cite
|
Sign up to set email alerts
|

The Jet-Driven Outflow in the Radio Galaxy SDSS J1517+3353: Implications for Double-Peaked Narrow-Line Active Galactic Nucleus

Abstract: We report on the study of an intriguing active galaxy that was selected as a potential multiple supermassive black hole merger in the early-type host SDSS J151709.20+335324.7 (z = 0.135) from a complete search for double-peaked [O III] lines from the SDSS spectroscopic QSO database. Ground-based SDSS imaging reveals two blue structures on either side of the photometric center of the host galaxy, separated from each other by about 5.7 kpc. From a combination of SDSS fibre and Keck/HIRES long-slit spectroscopy, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 37 publications
9
105
0
Order By: Relevance
“…This has been observed in several galaxies, on small and large scales (Nesvadba et al 2009;Tremblay et al 2009;Rosario et al 2010;Couto et al 2013;Reynaldi & Feinstein 2013;Santoro et al 2014). Theoretical studies are in agreement with this scenario, suggesting that the radio activity influences the energetics and thermodynamics of the hot, space-filling medium in these hosts (Reynolds et al 2002;Fragile et al 2004;Wagner & Bicknell 2011).…”
Section: Introductionsupporting
confidence: 52%
“…This has been observed in several galaxies, on small and large scales (Nesvadba et al 2009;Tremblay et al 2009;Rosario et al 2010;Couto et al 2013;Reynaldi & Feinstein 2013;Santoro et al 2014). Theoretical studies are in agreement with this scenario, suggesting that the radio activity influences the energetics and thermodynamics of the hot, space-filling medium in these hosts (Reynolds et al 2002;Fragile et al 2004;Wagner & Bicknell 2011).…”
Section: Introductionsupporting
confidence: 52%
“…A major obstacle in identifying binary AGNs using the NEL splitting signature, however, is that such profiles can also arise from NLR gas kinematics around single AGNs, such as rotating disks or bi-conical outflows (Axon et al 1998;Veilleux et al 2001;Crenshaw et al 2010;Shen et al 2011a;Rosario et al 2010;Fischer et al 2011;Smith et al 2011Smith et al , 2012. Nevertheless, our followup observations (Liu et al 2010a;Shen et al 2011a) of a subset of a systematically selected sample of 167 AGNs with double-peaked NELs (Liu et al 2010b; see also Smith et al 2010;Wang et al 2009), as well as studies by other groups Fu et al 2012), have demonstrated the feasibility and importance of combining higher resolution NIR imaging (Fu et al 2011a;Rosario et al 2011) and spatially resolved optical spectroscopy (Comerford et al 2012) to discriminate kpcscale binary AGNs from single-AGN-NLR gas kinematics.…”
Section: Systematic Searches For Kpc-scale Binary Agnsmentioning
confidence: 99%
“…Jet-cloud interactions are an important mechanism in producing double-peaked [O iii] lines (e.g., Stockton et al 2007;Rosario et al 2010). Although the radio-detected fraction of type-2 double-peaked AGNs is similar to that of the general type-2 AGN population (∼35%; Liu et al 2010b), Smith et al (2010) found that radio sources are three times overrepresented in type-1 double-peaked AGNs than in the general type-1 AGN population.…”
Section: Isolated Double-peaked Agnsmentioning
confidence: 99%
“…If double-peaked [O iii] emission is indicative of a binary AGN, such emission most likely represents systems with transverse separations of ∼100 pc to ∼10 kpc (Liu et al 2010a), because each fiber of the SDSS spectrograph covers only 3 on the sky. But double-peaked emission-line profile may also arise from other mechanisms, such as peculiar narrow-line regions, extended emission-line nebulae (e.g., Fu & Stockton 2009), or jet-cloud interactions (e.g., Stockton et al 2007;Rosario et al 2010).…”
Section: Introductionmentioning
confidence: 99%